Object/Product Identification for Stock Taking Activities using Object Recognition Concept - Muhammad Nashir Ardiansyah; Prafajar Sukssesanno Muttaqin; Murman Dwi Prasetio; Nia Novitasari (Jurnal Rekayasa Sistem & Industri, 2021)
Stock taking activity is as a routine product inspection activity to check the inventory accuracy and helpreduce the risks of stealing, damage, and obsolete inventories. This activity can be categorized as timeconsuming and expensive activity. In addition, this activity needs a lot of concentration and prone tohuman errors and mistakes. This study aims to replace human manual inspection in terms of object typeand quantity with objects identification to reduce errors, time, and costs. Digital image processing in theform of Object Recognition is used in this study to determine the type of object and the number of objects.The results showed that the detection rate of a single product reached 90% which was influenced by theangle of an image and the detection rate of object quantity reaches 81% in average in real environmentwith a certain condition. It is expected that costs of inventory inspection and warehousing activities can bereduced, as well as the improvement in terms of efficiency and effectiveness can be achieved.